2006
DOI: 10.1007/s10571-006-9121-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aspects of Prions, Their Receptor Molecules, and Innovative Approaches for TSE Therapy

Abstract: 1. Prion diseases are a group of rare, fatal neurodegenerative diseases, also known as transmissible spongiform encephalopathies (TSEs), that affect both animals and humans and include bovine spongiform encephalopathy (BSE) in cattle, scrapie in sheep, chronic wasting disease (CWD) in deer and elk, and Creutzfeldt-Jakob disease (CJD) in humans. TSEs are usually rapidly progressive and clinical symptoms comprise dementia and loss of movement coordination due to the accumulation of an abnormal isoform (PrP(Sc)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 179 publications
0
36
0
1
Order By: Relevance
“…LPB-p40 was localized on 40S ribosomes [7] and in the nucleus [8], while 67LR was located on the cell surface, where, in addition to its role as a high affinity laminin receptor, it was shown to function as the receptor for elastin [9] and as a positional marker for the differentiation of the fetal eye organ [10]. 37-kDa LRP was identified as a PrP c accomplice [11], and 37LBP/67LR acts as a receptor for PrP c [12] and infectious prions [13], as extensively reviewed elsewhere [14][15][16]. Additionally, 37LBP/67LR acts as a receptor for a number of viruses, including sindbis [17], dengue [18], and the adeno-associated virus serotypes 8, 2, 3, and 9 [19].…”
Section: Introductionmentioning
confidence: 99%
“…LPB-p40 was localized on 40S ribosomes [7] and in the nucleus [8], while 67LR was located on the cell surface, where, in addition to its role as a high affinity laminin receptor, it was shown to function as the receptor for elastin [9] and as a positional marker for the differentiation of the fetal eye organ [10]. 37-kDa LRP was identified as a PrP c accomplice [11], and 37LBP/67LR acts as a receptor for PrP c [12] and infectious prions [13], as extensively reviewed elsewhere [14][15][16]. Additionally, 37LBP/67LR acts as a receptor for a number of viruses, including sindbis [17], dengue [18], and the adeno-associated virus serotypes 8, 2, 3, and 9 [19].…”
Section: Introductionmentioning
confidence: 99%
“…12 Besides monoBesides monoclonal antibodies targeting the prion protein, 13,14 also single chain anti-PrP antibodies are currently investigated for a TSE therapy. 15 �mong many interaction partners identified for PrP c , 10,[16][17][18] the non-integrin 37/67 kDa laminin receptor (LRP/LR) has been discovered as a receptor for both the cellular PrP c 19,20 and the disease associated PrP Sc . 21,22 Downregulation of LRP/LR by antisense Downregulation of LRP/LR by antisense LRP RN� or siRN�s directed against LRP mRN� abrogates PrP Sc propagation in ScN2a cells.…”
Section: Introductionmentioning
confidence: 99%
“…None of the affected individuals can be treated or cured effectively (Ludewigs et al, 2007;Vana et al, 2007;Weissmann & Aguzzi, 2005). The abnormal form of the prion protein, PrP Sc , is frequently associated with infectivity and propagates mainly in the brain and the lymphoreticular system (LRS).…”
mentioning
confidence: 99%
“…We recently showed that blockage or downregulation of LRP/LR in neoplastic cells prevents invasion of these cells, suggesting that LRP/LR plays a major role in cancer metastasis (Zuber et al, 2008b) and (iv) finally, LRP/LR represents a key player in prion infection (Ludewigs et al, 2007;Vana et al, 2007;Zuber et al, 2007a). LRP has been shown to act both as the PrP c (Gauczynski et al, 2001b) and PrP Sc receptor (Gauczynski et al, 2006) and is responsible for bovine PrP Sc internalization by human enterocytes (Morel et al, 2005).…”
mentioning
confidence: 99%